Analysis Of Production Efficiency In Large Red Chili Farming In Kampili Village, Pallangga Subdistrict, Gowa Regency - Muh Saldi; Mohammad Natsir; Andi Amran Asriadi; Nailah; Muh. Rusman Al Aswar (Citakonsultindo, 2026)
This study aims to analyze the factors influencing large red chili pepper production and estimate the efficiency level of large red chili pepper farming in Kampili Village, Pallangga District, Gowa Regency. The sampling method used was 30 large red chili farmers. The sample size used in the study was 30 people, or 15% of the total population of large red chili farmers. The results of the regression analysis showed that not all input variables significantly influenced production (Y). The variables seed (X2), urea fertilizer (X3), and NPK Phonska fertilizer (X4) had a positive and significant effect on production, as their significance values ​​were less than 0.05. Meanwhile, the variables land area (X1), petroganic organic fertilizer (X5), demolish pesticide (X6), and labor (X7) did not have a significant effect, having a significance value greater than 0.05. Nevertheless, all regression coefficients were positive, indicating that all input variables tended to increase large red chili production. Meanwhile, input efficiency indicates that most production factors are not being utilized optimally. The variables land area (X1), seeds (X2), urea fertilizer (X3), Phonska NPK fertilizer (X4), Petroganic organic fertilizer (X5), and Demolish pesticide (X6) are inefficient, requiring increased utilization to achieve maximum production. Labor (X7) is inefficient, with an economic efficiency value of less than one, requiring reduction or more efficient management. Overall, large red chili farming still has opportunities to increase production and income through optimizing the use of production inputs, particularly land area, seeds, fertilizer, pesticides, and controlling labor costs.